2006
DOI: 10.1159/000088060
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Lung Uptake of Iodine-123 Metaiodobenzylguanidine in Patients with Myeloperoxidase Antineutrophil Cytoplasmic Antibodies-Positive Vasculitis

Abstract: Background: Iodine-123 metaiodobenzylguanidine (123I-MIBG) lung uptake in the early phase has been proposed as a potential marker of endothelial function because MIBG behaves qualitatively similarly to norepinephrine in pulmonary circulation. Objectives: The purpose of the present study was to examine the lung uptake of 123I-MIBG in patients diagnosed with myeloperoxidase antineutrophil cytoplasmic antibodies (MPO-ANCA)-associated vasculitis without clinical or radiological abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In a previous study from our laboratory, the mean value for early lung accumulation of 123 I‐MIBG in normal healthy volunteers was 1.45 ± 0.03 24 . The mean value for LMR in COPD patients in the present study (1.17 ± 0.03) was less than that in the normal control subjects, which was consistent with the findings of Arao et al 21 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a previous study from our laboratory, the mean value for early lung accumulation of 123 I‐MIBG in normal healthy volunteers was 1.45 ± 0.03 24 . The mean value for LMR in COPD patients in the present study (1.17 ± 0.03) was less than that in the normal control subjects, which was consistent with the findings of Arao et al 21 .…”
Section: Discussionsupporting
confidence: 92%
“…To quantify the lung uptake of 123 I‐MIBG, the lung to upper mediastinum ratio (LMR) of 123 I‐MIBG uptake was measured in the right and left lungs. The technique for estimating lung uptake of 123 I‐MIBG was similar to that reported previously 21,24,25 . The LMR was measured to assess the correlations with pulmonary function and pulmonary haemodynamic parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Second, the number of patients enrolled in this study was too small to detect endothelial damage by 123 I-MIBG lung uptake. We have demonstrated that only 6 cases of myeloperoxidase anti-neutrophil cytoplasmic antibodypositive vasculitis were enough to detect the impaired pulmonary endothelial function [8]. However, Takabatake et al [7] summarized 123 I-MIBG lung uptake in 23 patients with idiopathic pulmonary fibrosis and demonstrated significantly decreased 123 I-MIBG lung uptake in patients with idiopathic pulmonary fibrosis compared with controls.…”
Section: Discussionmentioning
confidence: 80%
“…Slosman et al initially evaluated lung uptake of 123 I-MIBG using animal models and demonstrated decreased 123 I-MIBG lung extraction in bleomycin-induced endothelial injury [6]. Furthermore, several clinical studies using this property of 123 I-MIBG scintigraphy showed that decreased 123 I-MIBG kinetics in the lung could serve as a novel diagnostic tool to evaluate the endothelial damage in patients with pulmonary fibrosis [7], myeloperoxidase anti-neutrophil cytoplasmic antibodypositive vasculitis [8], high altitude-related hypoxia [9], and high altitude pulmonary edema [10].…”
Section: Introductionmentioning
confidence: 99%
“…Scintigraphic assessment showed evidence of diminished uptake of 123 I-MIBG in the lungs of patients suffering from COPD [9,11], but also in patients with pulmonary fibrosis [12], vasculitis [13], high altitude pulmonary edema [14,15], chronic hypoxia [16] and after radiotherapy [17]. In other diseases, increased or prolonged retention of MIBG has been shown.…”
Section: Scintigraphymentioning
confidence: 99%